Thomas Wilson descriptive account and photograph - Wilson, Thomas, army officer
Photograph and descriptive account of Robert E. Lee's surrender at Appomattox, Va.
In part, typewritten transcript.
Army officer.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lee, Robert E. -- 1807-1870.; Appomattox (Va.) -- History -- Civil War, 1861-1865.; Army officers